Managing Fungal Infections in Cystic Fibrosis Patients: Challenges in Clinical Practice - Magee, Lauren C (Infect Drug Resist, 2021)
Cystic Fibrosis (CF) is an autosomal recessive disease characterized by a mutation in the cystic fibrosis transmembrane conductance regulator (CFTR) protein. Impairment of the CFTR protein in the respiratory tract results in the formation of thick mucus, development of inflammation, destruction of bronchial tissue, and development of bacterial or fungal infections over time. CF patients are commonly colonized and/or infected with fungal organisms, Candida albicans or Aspergillus fumigatus, with prevalence rates ranging from 5% to 78% in the literature. Risk factors for acquiring fungal organisms include older age, coinfection with Pseudomonas aeruginosa, prolonged use of oral and inhaled antibiotics, and lower forced expiratory volume (FEV(1)). There are limited data available to differentiate between contamination, colonization, and active infection. Furthermore, the pathogenicity of colonization is variable in the literature as some studies report a decline in lung function associated with fungal colonization whereas others showed no difference. Limited data are available for the eradication of fungal colonization and the treatment of active invasive aspergillosis in adult CF patients. In this review article, we discuss the challenges in clinical practice and current literature available for laboratory findings, clinical diagnosis, and treatment options for fungal infections in adult CF patients.